Reconstructive and Aesthetic Surgeries on the Female GenitaliaGuideline of the DGGG, DGPRAC, OEGGG and SGGG (S2k-Level, AWMF Registry No. 009/019, May 2022) - Beckmann, Matthias; Borkenhagen, Ada; Fahlbusch, Christine; Gold, Daniela; Hoffmann, Juergen; Löhrs, Bettina; Luze, Hanna; Mirastschijski, Ursula; O'Dey, Dan M.; Pöschke, Patrik; Remmel, Eugenia; Schaefer, Dirk; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Aim This official guideline was coordinated and published by the German Society for Gynaecology and Obstetrics (DGGG), the German Society for Plastic, Reconstructive and Aesthetic Surgery (DGPRAC), the Austrian Society for Gynaecology and Obstetrics (OEGGG), and the Swiss Society for Gynaecology and Obstetrics (SGGG). The guideline aims to provide a consensus-based overview of reconstructive and aesthetic surgeries on female genitalia based on an evaluation of the relevant literature. Methods This S2k-guideline was developed by representative members from different medical professions on behalf of the guidelines commission of the DGGG, DGPRAC, OEGGG and SGGG using a structured consensus process. Recommendations Statements and recommendations on the epidemiology, aetiology, classification, symptoms, diagnosis, and treatment of acquired changes of the external genitalia are presented and special situations are discussed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: aesthetic surgeries; female genital mutilation (FGM); female genitalia; guideline; reconstructive surgeries